2020
DOI: 10.3390/ai1030027
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Approach to Detect COVID-19 Patients from Chest X-ray Images

Abstract: Deep Learning has improved multi-fold in recent years and it has been playing a great role in image classification which also includes medical imaging. Convolutional Neural Networks (CNNs) have been performing well in detecting many diseases including coronary artery disease, malaria, Alzheimer’s disease, different dental diseases, and Parkinson’s disease. Like other cases, CNN has a substantial prospect in detecting COVID-19 patients with medical images like chest X-rays and CTs. Coronavirus or COVID-19 has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 60 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…Images of the chest were produced by Narin et al [7] , and ResNet50 identification of X-ray signals showed a 98% CO2 signal detection rate. Haque and Abdelgawad compared the CNN model for a COVID-19 positive patient [8] . This technique successfully finds and identifies patients who have Coronaviruses with almost no time or effort.…”
Section: Literature Surveymentioning
confidence: 99%
“…Images of the chest were produced by Narin et al [7] , and ResNet50 identification of X-ray signals showed a 98% CO2 signal detection rate. Haque and Abdelgawad compared the CNN model for a COVID-19 positive patient [8] . This technique successfully finds and identifies patients who have Coronaviruses with almost no time or effort.…”
Section: Literature Surveymentioning
confidence: 99%
“…Haque and Abdelgawad [ 24 ] have proposed a custom convolutional neural network model to detect COVID-19 patients using two different datasets containing normal and COVID-19 positive images. The proposed model achieved an accuracy of 98.3% using a second dataset.…”
Section: Related Literaturementioning
confidence: 99%
“…However, the paper considered a small dataset and did not specify the data source used. Haque and Abdelgawad [ 38 ] also provided binary classification using transfer learning, which is a technique to initialize the weights of a network based on a model pre-trained on a larger dataset and then fine-tuning it according to new and specific information [ 39 ]. Although the authors analyzed two distinct sets of images, only one database was used in each class, which may bias the created model.…”
Section: Overview Of Cnn and Covid-19 Diagnostic Modelsmentioning
confidence: 99%